DISTRIBUIÇÃO GEOGRÁFICA E AUTOECOLOGIA DE Desmodus rotundus É. GEOFFROY, 1810 (MAMMALIA: CHIROPTERA ) NOS BIOMAS BRASILEIROS - GONÇALVES DE CASTRO, Igor Vinícius; DIAS, Rosa Maria; PEREIRA DA SILVA, Elifas Augusto; ORTÊNCIO FILHO, Henrique; KASHIWAQUI, Elaine Antoniassi Luiz (ANAIS DO ENIC, 2025)
-